A hybrid deep learning paradigm for carotid plaque tissue characterization and its validation in multicenter cohorts using a supercomputer framework. (February 2022) - Skandha, Sanagala S.; Nicolaides, Andrew; Gupta, Suneet K.; Koppula, Vijaya K.; Saba, Luca; Johri, Amer M.; Kalra, Manudeep S.; Suri, Jasjit S.
Abstract: Background: Early and automated detection of carotid plaques prevents strokes, which are the second leading cause of death worldwide according to the World Health Organization. Artificial intelligence (AI) offers automated solutions for plaque tissue characterization. Recently, solo deep learning (SDL) models have been used, but they do not take advantage of the tandem connectivity offered by AI's hybrid nature. Therefore, this study explores the use of hybrid deep learning (HDL) models in a multicenter framework, making this study the first of its kind. Methods: We hypothesize that HDL techniques perform better than SDL and transfer learning (TL) techniques. We propose two kinds of HDL frameworks: (i) the fusion of two SDLs (Inception with ResNet) or (ii) 10 other kinds of tandem models that fuse SDL with ML. The system Atheromatic™ 2.0HDL (AtheroPoint, CA, USA) was designed on an augmentation framework and three kinds of loss functions (cross-entropy, hinge, and mean-square-error) during training to determine the best optimization paradigm. These 11 combined HDL models were then benchmarked against one SDL model and five types of TL models; thus, this study considers a total of 17 AI models. Results: Among the 17 AI models, the best performing HDL system was that comprising CNN and decision tree (DT), as its accuracy and area-under-the-curve were 99.78 ± 1.05% and 0.99 ( p <0.0001), respectively. These values are 6.4% and 3.2% better than those recorded for the SDL and TL models, respectively. We validated the performance of the HDL models with diagnostics odds ratio (DOR) and Cohen and Kappa statistics; here, HDL outperformed DL and TL by 23% and 7%, respectively. The online system ran in <2 s. Conclusion: HDL is a fast, reliable, and effective tool for characterizing the carotid plaque for early stroke risk stratification. Highlights: Fusion of deep learning with ten kinds of machine learning classifiers. Fusion of Inception and ResNet. Three kinds of loss functions such as cross-entropy loss, hinge loss, or mean-squared-error loss, and hypothesis was validated. These overall paradigms of hybrid deep learning were tried on multicenter study. 17 kinds of plaque tissue characterization for symptomatic vs. asymptomatic tissue classification models.